Menjaga Aliran Merawat Budaya Bengawan : Implementasi Deep Learning Melalui Ko Kurikuler Lintas Mapel di SMPN 21 Surakarta - Wegang Sri Sulanjari; Lukit Adi Syam Ari; Muh Nur Azis Yusuf; Ghufron Ahmad Al Muzakki; Evylia Ratna Arjantir; Sabar Narimo; Sofyan Anif (Jurnal Ragam Pengabdian, 2026)
Deep learning emphasizes the connection between academic knowledge and students’ socio-ecological realities. This study aims to describe the implementation of a cross-subject co-curricular project for eighth-grade students at SMP Negeri 21 Surakarta, Indonesia, which is centered on the Bengawan Solo River as a contextual learning resource. The research employed a descriptive qualitative case study approach. Data were collected through participatory observation, document analysis, and in-depth interviews with key informants, including the former Mayor of Surakarta, F.X. Hadi Rudyatmo, local government officials, and community leaders living along the riverbank. Students were organized into five thematic research groups examining the historical, ecological, social, biological, and tourism dimensions of the river ecosystem. The findings reveal that interdisciplinary learning through field-based inquiry enhances students’ critical literacy, ecological awareness, and social empathy. The geographical proximity of the school to the Bengawan Solo River was transformed into a living laboratory where students conducted authentic investigations and produced various differentiated learning outputs, including research reports, short documentary films, digital infographics, artistic performances, and community presentations. The culmination of the project was a public exhibition attended by community members, which functioned as an authentic assessment platform demonstrating students’ ability to reinterpret local historical narratives and environmental issues into creative and practical solutions. This study highlights the potential of integrating deep learning with place-based education to foster contextual understanding, environmental responsibility, and higher-order thinking skills among secondary school students.